Endothelin-1 Promotes Myofibroblast Induction through the ETA Receptor via a rac/Phosphoinositide 3-Kinase/Akt-dependent Pathway and Is Essential for the Enhanced Contractile Phenotype of Fibrotic Fibroblasts - Shi-Wen, Xu (The American Society for Cell Biology, 2004)
The endothelins are a family of endothelium-derived peptides that possess a variety of functions, including vasoconstriction. Endothelin-1 (ET-1) is up-regulated during tissue repair and promotes myofibroblast contraction and migration, hence contributing to matrix remodeling during tissue repair. Here, we show that addition of ET-1 to normal lung fibroblasts induces expression of proteins that contribute to a contractile phenotype, including α-smooth muscle actin (α-SMA), ezrin, moesin, and paxillin. We confirm that ET-1 enhances the ability of lung fibroblasts to contract extracellular matrix, a function essential for tissue repair, through induction of de novo protein synthesis. Blockade of the Akt/phosphoinositide 3-kinase (PI3-kinase) pathway with LY294002 and wortmannin prevents the ability of ET-1 to induce α-SMA, ezrin, paxillin, and moesin and to promote matrix contraction. Dominant negative rac and Akt blocked the ability of ET-1 to promote formation of α-SMA stress fibers. Using specific ET-1 receptor inhibitors, we show that ET-1 induces collagen matrix contraction through the ETA, but not the ETB, receptor. Relative to normal pulmonary fibroblasts, fibroblasts cultured from scars of patients with the fibrotic disease systemic sclerosis (scleroderma) show enhanced ET-1 expression and binding. Systemic sclerosis lung fibroblasts show increased ability to contract a collagen matrix and elevated expression of the procontractile proteins α-SMA, ezrin, paxillin, and moesin, which are greatly reduced by antagonizing endogenous ET-1 signaling. Thus, blocking ET-1 or the PI3-kinase/Akt cascades might be beneficial in reducing scar formation in pulmonary fibrosis.